2005
DOI: 10.1159/000080490
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Increases Glutathione Peroxidase Enzyme Activity and Decreases Lipid Peroxidation Levels in Hypoxic-Ischemic Brain Injury in Neonatal Rats

Abstract: Background: We have previously shown that erythropoietin (Epo) exerts neuroprotective effects in the Rice-Vannucci model of neonatal hypoxic-ischemic brain injury. However, the mechanisms of Epo protection in this model are still unclear. Objectives: In the present study, we studied the effects of systemically administered Epo on lipid peroxidation levels and antioxidant enzyme (superoxide dismutase and glutathione peroxidase) activities following hypoxic-ischemic brain injury in neonatal rats. Methods: Seven-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
75
0
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 24 publications
3
75
0
6
Order By: Relevance
“…Activation of the Janus kinase/Stat5 pathway, along with nuclear factor kappa B (NFkB) and Akt phosphorylation, appears to be responsible for reduced apoptotic cell death after Epo. 38,39 Other acute neuroprotective mechanisms include antiinflammatory, 40,41 antiexcitotoxic, 42 and antioxidant 43 effects. Epo also stimulates growth factors 44,45 and enhances neurogenesis, angiogenesis, and long-term repair and plasticity, thus providing neuroprotective and trophic effects that last well beyond the acute period of injury.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the Janus kinase/Stat5 pathway, along with nuclear factor kappa B (NFkB) and Akt phosphorylation, appears to be responsible for reduced apoptotic cell death after Epo. 38,39 Other acute neuroprotective mechanisms include antiinflammatory, 40,41 antiexcitotoxic, 42 and antioxidant 43 effects. Epo also stimulates growth factors 44,45 and enhances neurogenesis, angiogenesis, and long-term repair and plasticity, thus providing neuroprotective and trophic effects that last well beyond the acute period of injury.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this finding, rhEPO treatment in rats with cisplatin-induced (12,13) or ischemia-and reperfusion-induced (14) acute renal failure enhances their functional recovery. Moreover, in contrast to the concerns about the rhEPO treatment-associated potential deterioration of renal function (15), clinical studies have reported that rhEPO could retard disease progression to chronic renal failure (16 -18) by anemia correction (19), proangiogenic properties (20 -22), reduction of oxidative stress (23), and antiapoptotic effects (24 -26). However, it is unknown whether the beneficial effects of rhEPO in chronic renal diseases are related to the inhibition of EMT.…”
mentioning
confidence: 99%
“…Ehrenreich [32] have demonstrated that EPO achieves its protective effects via its antioxidant, anti-apoptotic effects rather than by regulating disease-specific pathological mechanisms. Similarly, Kumral et al [33] have reported that EPO increases GPx activity and decreases lipid peroxidation in neonatal rats exposed to hypoxia compared with controls. Kuzugüden et al [34] have shown the oxidative stress induced by high doses of thinner can be reduced by EPO via a decrease in the formation of MDA and an increase in GPx activity in rat brain.…”
Section: Discussionmentioning
confidence: 79%